2018
DOI: 10.17755/esosder.386067
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmen Adaylarinin Çokkültürlülüğe İli̇şki̇n Tutumlari

Abstract: Bu araştırmada, öğretmen adaylarının çokkültürlülüğe yönelik tutumlarının bazı değişkenlere göre incelenmesi amaçlanmıştır. Araştırmada tarama modeli kullanılmıştır. Araştırmanın çalışma grubu, 2015-2016 bahar yarıyılında Kafkas Üniversitesi Eğitim Fakültesinde birinci sınıftan dördüncü sınıfa kadar öğrencisi bulunan Okul Öncesi Öğretmenliği, Sınıf Öğretmenliği, Fen Bilgisi Öğretmenliği, Sosyal Bilgiler Öğretmenliği ve Psikolojik Danışma ve Rehberlik programlarından oluşmaktadır. Araştırma, ilgili programların… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
7
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 13 publications
1
7
0
2
Order By: Relevance
“…Participants in these two regions were significantly more positive towards multiculturality, particularly in the "Richness" (Southeastern Anatolia) and "Threat" (Southeastern and Eastern Anatolia) dimensions than participants in other regions. Similarly, Güngör, Buyruk and Özdemir (2018) concluded that the teacher candidates from Southeastern and Eastern Anatolian regions have a more positive attitude than teacher candidates from the other regions. Particularly when the results concerning parental educational status are considered regarding the reflections of the nation state ideology on education, it may be inferred that participants in these two regions whose parents stayed outside the school system (literate and illiterate) were less intensely affected by the formal ideology of the state and therefore less influenced by the homogenization and "otherizing" of education, and displayed more positive attitudes towards different identities and class groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants in these two regions were significantly more positive towards multiculturality, particularly in the "Richness" (Southeastern Anatolia) and "Threat" (Southeastern and Eastern Anatolia) dimensions than participants in other regions. Similarly, Güngör, Buyruk and Özdemir (2018) concluded that the teacher candidates from Southeastern and Eastern Anatolian regions have a more positive attitude than teacher candidates from the other regions. Particularly when the results concerning parental educational status are considered regarding the reflections of the nation state ideology on education, it may be inferred that participants in these two regions whose parents stayed outside the school system (literate and illiterate) were less intensely affected by the formal ideology of the state and therefore less influenced by the homogenization and "otherizing" of education, and displayed more positive attitudes towards different identities and class groups.…”
Section: Resultsmentioning
confidence: 99%
“…In Turkey, studies oriented towards defining individuals' perceptions, attitudes, and views on multiculturality have been undertaken by academicians, prospective teachers, school administrators and teachers (Akkaya, Kırmızı & İşçi, 2018;Aslan, 2017;Avcı & Faiz, 2018;Coşkun, 2012;Damgacı & Aydın, 2013;Demir 2012;Demir & Başarır, 2013;Demirsoy, 2013;Güngör, Buyruk & Özdemir, 2018;Kahraman & Sezer, 2017;Karaçam & Koca, 2012;Kaya & Söylemez, 2014;Nayır & Çetin, 2018;Özdemir & Dil, 2013;Polat, 2012;Üzülmez & Karakuş, 2018), and the extent to which curricula and textbooks include multiculturality was investigated (Açıkalın, 2010;Akar & Keyvanoğlu, 2016;Akhan & Yalçın, 2016;Cırık, 2008;Çayır, 2016;Keskin & Yaman, 2014;Seban & Uyanık, 2016). These studies have shown that while Turkish teacher candidates, teachers, administrators and academicians view multiculturality and multicultural education in a positive light, curricula and textbooks have many deficiencies.…”
mentioning
confidence: 99%
“…Akar, 2017;Akkaya, Susar Kırmızı & İşçi, 2018;Başarır, Sarı & Çetin, 2014;Marangoz, Aydın & Adıgüzel, 2015), attitudes (e.g. Durmuş, 2017;Güleç, 2019;Güngör, Buyruk & Özdemir, 2018;Kaba, 2019;Kervan, 2017;Koçak & Özdemir, 2015;Köşker & Özgen, 2018;Onur Sezer & Bağçeli Kahraman, 2017;Siviş, 2019) and competencies (e.g. Başarır, 2012;Başbay & Bektaş, 2009;Bulut, 2014;Ekinci, 2019;Karadağ, 2019;Polat & Kılıç, 2013;Tari, 2019;Yılmaz, 2016) of educators towards multiculturalism, scale development or adaptation studies regarding multiculturalism (e.g.…”
Section: Multicultural Education In Social Studies Coursementioning
confidence: 99%
“…Ulusal literatür incelendiğinde, çeşitli branşlarda öğrenim gören öğretmen adaylarının, kültürel farklılık ve zenginlik kavramlarına ilişkin algılarının belirlendiği (Meydan & Yıldırım, 2014;Öztürk & Günel, 2016;Rengi & Polat, 2014), çeşitli tutum ve değişkenler bakımından kültürlerarası duyarlılık ve etnik merkezcilik düzeylerinin ölçüldüğü (Akın, 2016;Boran & Arcagök, 2017;Çoban, Güney-Karaman & Doğan, 2010;Demir & Üstün, 2017;Öğüt & Olkun, 2018;Rengi & Polat, 2014;Yılmaz & Göçen, 2013), çok kültürlülük ve çok kültürlü eğitime yönelik algı, tutum ve eğilimlerinin belirlendiği (Akkaya, Susar-Kırmızı & İşçi, 2018;Başar, 2019;Demirsoy, 2013;Güngör, Buyruk & Özdemir, 2018;Ünlü & Örten, 2013, Ürey, 2017, küresel vatandaşlık eğitimine ilişkin görüşlerinin incelendiği (Çolak, Kabapınar & Öztürk, 2019;Gürdoğan-Bayır, Göz & Bozkurt, 2014;Egüz, 2016) bazı çalışmalara rastlanılmaktadır. Yapılan araştırmalarda, özellikle öğretmen adaylarının diğer kültürlere olan yaklaşımlarının belirlenmesinde daha çok nicel araştırma desenlerinin tercih edildiği buna karşın, sınırlı sayıda nitel odaklı çalışmaların (İbrahimoğlu, 2018) yapıldığı belirlenmiştir.…”
Section: Introductionunclassified